Involvement of Serotonin Transporter Gene Polymorphisms (5-HTT) in Impulsive Behavior in the Japanese Population - Nomura, Michio (PLoS One, 2015)
The serotonergic pathway has been implicated in the pathogenesis of impulsivity, and sensitivity to aversive outcomes may be linked to serotonin (5-HT) levels. Polymorphisms in the gene that encodes the serotonin transporter (5-HTT), which have differential effects on the level of serotonin transmission, display alternate responses to aversive stimuli. However, recent studies have shown that 5-HT does not affect motor function, which suggests that the functioning of the serotonin-transporter-linked polymorphic region (5-HTTLPR) does not directly affect the behavioral regulatory process itself, but instead exerts an effect via the evaluation of the potential risk associated with particular behavioral outputs. The aim of the present study was to examine the effect of specific 5-HTTLPR genotypes on the motor regulatory process, as observed during a Go/Nogo punishment feedback task. 5-HTT gene-linked promoter polymorphisms were analyzed by polymerase chain reaction, using lymphocytes from 61 healthy Japanese volunteers. Impulsivity was defined as the number of commission errors (responding when one should not) made during a Go/Nogo task. We found that the s/s genotype group made fewer impulsive responses, specifically under aversive conditions for committing such errors, compared to those in the s/l group, without affecting overall motor inhibition. These results suggest that 5-HTTLPRs do not directly affect the behavioral regulatory process itself, but may instead exert an effect on the evaluation of potential risk. The results also indicate that under such aversive conditions, decreased expression of 5-HTT may promote motor inhibitory control.